The impact of the Brummeria Renaissance case in determining whether the receipt of an interest-free loan results in gross income accruing to the borrower - Smit, Sybrand Abraham (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm) -- Stellenbosch University, 2008.